Editors of Special Issue - of Special Issue, Editors (Journal of Science and Technology, 2017)
EditorsSpecial Issue of Journal of Science and TechnologyIssue on the Application of Science and Mathematics  Editor In ChiefDr. Suzi Salwah Binti JikanUniversiti Tun Hussein Onn Malaysia Editors Assoc. Prof. Dr. Kavikumar S/O JacobUniversiti Tun Hussein Onn Malaysia Dr. Phang ChangUniversiti Tun Hussein Onn Malaysia Dr. Norhayati Binti MuhammadUniversiti Tun Hussein Onn Malaysia Dr. Hazel Monica Matias-PeraltaUniversiti Tun Hussein Onn Malaysia Dr. Nurun Najwa Binti RuslanUniversiti Tun Hussein Onn Malaysia Dr. Maria Elena Binti NorUniversiti Tun Hussein Onn Malaysia Dr. Norazlin Binti AbdullahUniversiti Tun Hussein Onn Malaysia Dr. Amira Saryati Binti AmeruddinUniversiti Tun Hussein Onn Malaysia Dr. Saliza Binti AsmanUniversiti Tun Hussein Onn Malaysia Dr. Shakila Binti AbdullahUniversiti Tun Hussein Onn Malaysia Dr. Nurul Nadia Binti AdnanUniversiti Tun Hussein Onn Malaysia